DEVELOPMENT OF SPEAKING COMPETENCE OF STUDENTS THROUGH STUDYING PAHLAVAN MAHMUD'S RUBAI - Sulaymonova Nafisa Sattorovna NDPI academic lyceum teacher of native language and literature. Navoi city (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2024)
This scientific article reflects on the methods of forming the elements of speech competence through an innovative approach in teaching the students of the academic lyceum the grace of Pahlavon Mahmud rubai, the skill of choosing words, the use of artistic image tools, and the methods of creating skills. It is shown that the tools of artistic imagery in lyrics, the masterpieces of poetic art, reveal their inner, hidden abilities of students and encourage them to think creatively and come up with promising ideas. KEY WORDS: competence, «Autofocus method», lojuvard, drunk, foolish , zeru dast, zunnor, target.